Inovasi Pupuk Organik Berbasis Kelapa Sawit di Maluku Utara - Arifin, Tuti Handayani; Fatmawati, Mila; Rasulu, Hamidin; Gunawan, Gunawan; Sapsuha, Yusri; Darsan, Ismi Musdalifa (Jurnal Pertanian Khairun, 2025)
This study aims to examine the potential, production process, agronomic benefits, and challenges in the implementation of palm oil-based organic fertilizers in North Maluku through a literature review. By gathering and analyzing the latest literature, this study presents findings on key solutions to address land degradation and dependence on chemical fertilizers that negatively impact the environment. The literature review results highlight the positive potential of palm oil waste, its agronomic benefits, contributions to climate change mitigation, reduction of environmental pollution, and the challenges and opportunities in North Maluku. The study concludes that with the right policy support and the adoption of technology by farmers, palm oil-based organic fertilizers can be a strategic solution to achieve more sustainable and productive agriculture.